DISEMINASI TEKNOLOGI PAKAN BUATAN ALTERNATIF UNTUK PENGEMBANGAN BUDIDAYA IKAN GURAME INTENSIF DALAM UPAYA MENINGKATKAN PRODUKTIVITAS PERIKANAN DI KELURAHAN LIMAU MANIS KECAMATAN PAUH KOTA PADANG - Efrizal Efrizal; Nurmiati Nurmiati; Chairul Chairul; Anthoni Agustien; Suwirmen Suwirmen; Rusnam Rusnam; Deswati Deswati (LPPM Universitas Andalas, 2020)
Lecturer and community based science and technology activities (IbDM) were carried out with the aim of disseminating technology for Gurame culture intensively in an effort to increase fisheries productivity in Limau Manis, Pauh Subdistrict, Padang City and increase the knowledge and skills of fish farmers (community) in Koto Tangah Village in the field of Gurame fish maintenance business in West Sumatra, so that they are expected to be able to carry out maintenance in a good / environmentally friendly manner. Besides this IbDM activities are also expected to be able to reduce operational costs in maintaining Nirwana Tilapia and in the end can increase the income of the farmers (community) of Limau Manis Village through the development of sustainable fish farming. To achieve optimal technology dissemination results, the main target of IbDM in Pauh Subdistrict is fish farmer groups and community leaders / leaders of Limau Manis Village who are expected to be able to motivate farmers to socialize the method of making alternative formula feeds for intensive development of Nirwana Tilapia aquaculture and environmentally friendly. The methods used in this activity are (1) counseling, with the main material: (a) providing knowledge of various kinds of raw materials that can be used for fish food, (b) providing knowledge about the preparation of artificial food formulas / compositions, ( c) provide knowledge about the process of making artificial food (d) increase public knowledge about how to store pellets that are good to be more durable and (e) provision of material on testing the quality of feed, both physically, chemically and biologically; and (2) Intensive demonstration of making alternative pellet feeds for Nirwana Tilapia aquaculture. From the results of the IbDM activity, it was found that the knowledge and skills of farmer groups in Limau Manis Sub-district, Kec. Pauh, Padang before the IbDM activities were carried out was still very low. However, the motivation or desire of the community of IbDM partner farmer groups to carry out the culture or maintenance of fish is very large. This can be seen from the desire of the IbDM partner farmer group to master the technology of making fish feed from the results of leaf waste and taro stems which are processed into flour relatively high. Furthermore, the results of IbDM activities in the community can increase the knowledge and skills of the community in finding alternative feed for fish feed so that culture activities can run well in IbDM partner areas. In order for aquaculture to run well in partner areas of IbDM, it is necessary to carry out IbDM activities continuously on the techniques of making alternative fish pellets and efficient and effective fish-raising techniques. Besides that, it needs financial support or credit by the authorities to the community or fish farmers for capital to develop their businesses.